Crime Stoppers: A National Evaluation of Program Operations and Effects, (United States), 1984 - Rosenbaum, Dennis P. ([Verlag nicht ermittelbar], 1990)
The goal of this data collection was to answer three basic questions about the Crime Stoppers (CS) program, a program encouraging citizen involvement in averting crime and apprehending suspects. First, how does Crime Stoppers work in theory and in practice? Second, what are the opinions and attitudes of program participants toward the Crime Stoppers program? Third, how do various components of the program such as rewards, anonymity, use of informants, and media participation affect criminal justice outcome measures such as citizen calls and arrests? This collection marks the first attempt to examine the operational procedures and effectiveness of Crime Stoppers programs in the United States. Police coordinators and board chairs of local Crime Stoppers programs described their perceptions of and attitudes toward the Crime Stoppers program. The Police Coordinator File includes variables such as the police coordinator's background and experience, program development and support, everyday operations and procedures, outcome statistics on citizen calls (suspects arrested, property recovered, and suspects prosecuted), reward setting and distribution, and program relations with media, law enforcement, and the board of directors. Also available in this file are data on citizen calls received by the program, the program's arrests and clearances, and the program's effects on investigation procedure. The merged file contains data from police coordinators and from Crime Stoppers board members. Other variables include city population, percent of households living in poverty, percent of white population, number of Uniform Crime Reports (UCR) Part I crimes involved, membership and performance of the board, fund raising methods, and ratings of the program.